2016
DOI: 10.1039/c6tb00113k
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered drug delivery coatings composed of daidzein-loaded PHBV microspheres embedded in a biodegradable polymer matrix by electrophoretic deposition

Abstract: The development of drug delivery coating systems for local and long-term drug release is gaining increasing interest especially to functionalize bioinert implants with osseointegration and antibacterial properties. In this study, a biodegradable drug delivery coating platform consisting of drug-loaded PHBV microspheres embedded in an alginate-PVA matrix was fabricated by a one-step electrophoretic deposition (EPD) process. Layer by layer (LbL) deposition was exploited to generate chitosan-alginate multilayers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…According to the long-term BMP2 release test, we could conclude that BMP2 was successfully immobilized on GF during EPD and released in a controlled manner for up to 10 days. The long-term release curve represented a typical diffusion-based release characteristic which is in agreement with the Peppas equation and our previous investigation, indicating a diffusion-based release mechanism. Additionally, our electroresponsive release experiment presented significantly different BMP2 release behaviors influenced by the electric field.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the long-term BMP2 release test, we could conclude that BMP2 was successfully immobilized on GF during EPD and released in a controlled manner for up to 10 days. The long-term release curve represented a typical diffusion-based release characteristic which is in agreement with the Peppas equation and our previous investigation, indicating a diffusion-based release mechanism. Additionally, our electroresponsive release experiment presented significantly different BMP2 release behaviors influenced by the electric field.…”
Section: Discussionsupporting
confidence: 90%
“…EPD is a simple, rapid, and room-temperature coating technique that involves the movement of charged particles/molecules under an appropriate electric field, leading to their consolidation on the oppositely charged electrode to form films and coatings with high microstructural homogeneity and tailored thickness . With the proper design of EPD suspension, e.g., the addition of polyelectrolytes (chitosan “+” or alginate “–”) which act as the charger in suspension and as the binder in the deposit, functional molecules dispersed in EPD suspension are able to migrate and robustly bonded to the oppositely electrode under an electric field. Furthermore, the presence of amino or carboxylic groups on polyelectrolyte chains facilitated the pH-responsive property of the deposited coatings, which could be used to design stimuli-responsive drug delivery systems. Combining the conductive charter of GF and the pH sensitivity of EPD coatings, it is expected that the electric field exerted on GF may play a role in controlling the BMP2 release from the deposited coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Huang et al reported that PHBV applications in the microsphere form to improve the bone conduction and mechanical strength of PLGA scaffolds, and their results showed that this ability increased from about 30% to 80% (Huang, Shi, Ren, Du, & Wang, ). We tried to introduce a cell‐co‐polymer construct that has a great ability for use in bone tissue engineering applications, however, several studies were also tried to improve PHBV osteoconductivity or mechanical properties by blending with other polymers or nano‐composites such as calcium phosphate and gelatin (Duan & Wang, ), PLLA and collagen (Sultana, ), bioactive glass (J. Wu, Wu, Xue, Li, & Liu, ), nano strontium carbonate and Platelet Rich Plasma layer (Sajesh, Kiran, Nair, & Jayakumar, ) and daidzein and PVA (Chen et al, ) for bone tissue engineering application. However, our results demonstrated PHBV alone can be used in bone tissue engineering with appropriate stem cells cultured on it, and this strategy is better than manipulation of the PHBV, whereas its properties could be modified and its degradation products can be turned into harmful.…”
Section: Discussionmentioning
confidence: 99%
“…29 Numerous studies have reported the use of LbL assembly to incorporate proteins, growth factors, polysaccharides, nucleic acids, and functional peptides into biomaterials, and to deposit coatings with controlled degradation rates. [30][31][32][33][34] In addition, the physicochemical properties of multilayer films such as topography, stiffness and strength, and hydrophobicity can be optimized by altering the coating composition and processing parameters, which in turn enables control over biological cellular responses. 35,36 The bone tissue engineering field faces numerous challenges including difficulties of in vitro cell culture, mimicking osteogenesis in native tissue, the cost and complexity of manufacturing, and achieving biomaterial scaffolds that satisfy the diverse structural, mechanical and biological properties required for bone tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%